The Use of Location-Based Augmented Reality as Information Media in The Digital Map Application of Jakabaring Sport City - Arifiani, Siska; Manurung, Miranda; Ginardi, Raden Venantius Hari (LPPM Universitas Islam 45 Bekasi, 2021)
Jakabaring Sport City (JSC) is an integrated sports facility complex and a public tourist spot in Palembang. Due to its extensive area and numerous facilities, visitors need a map with distinct markers for the landmark to make it easier when walking around. Recent technology advancements and its expanding role in various fields invites the question on how to integrate technology in the tourism industry. This journal aims to create an android-based digital map application with augmented reality (AR) as a guiding medium that will display directions towards the Jakabaring exit gate. This app is built using Maps SDK for Android to build the digital maps, Navigation SDK for Android to run navigation, and Maps for Unity to display AR objects that will show the directions towards the exit. The development focuses on a location-based service using GPS to track the user's whereabouts and provide real-time location data around the user. This application has a location search feature, a guiding direction (route and navigation) to a designed location, and an AR camera feature to display where the JSC exit gate is located. Every feature is working well and able to help users while visiting JSC. However, this application could still be improved in the AR feature because on its current version, it is only able to display directions to the JSC exit gate when users are within a radius of one kilometer or less to the exit.